BUKU SAKU BANGUN RUANG SISI DATAR BERBASIS AUGMENTED REALITY - Andri Ramadhan (LPD IKIP PGRI Pontianak, 2023)
This study aims to find out the initial description of the learning process and students' understanding of mathematics, especially the flat side building material, the initial product, validity, practicality and effectiveness as well as the final product of the BanG AR pocket book and application on flat sided space build material. The subjects in this study were mathematics teachers and students in class VI I I F of SMP Negeri 19 Pontianak, totaling 14 students. The method used in this research is the Research & Development method (1) analysis, (2) design, (3) development, (4) implementation, and (5) evaluation. The results of the research that has been carried out show that the development of pocket book learning media and the BanG AR application supports the teaching and learning process at the school. Based on the assessment of media and material experts on the pocket book and the BanG AR application, a combined index percentage of 90% with very valid criteria was obtained. Teacher responses obtained an average score of 4.83 with very practical criteria, and student responses obtained an average score of 4.27 with very practical criteria. And the effectiveness of obtaining an index presentation of 78.57% of students passed the posttest after learning to use the pocket book and the BanGAR application . This shows that the developed BanG AR pocket book and application are valid, practical, and effective for use in the mathematics learning process, especially in the material of flat sided spaces.